2020
DOI: 10.14744/nci.2020.23590
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of ischemia-modified albumin levels to disease activity scores and HLA-B27 in patients with ankylosing spondylitis

Abstract: The relationship of ischemia-modified albumin levels to disease activity scores and HLA-B27 in patients with ankylosing spondylitis Orıgınal Article PT&R Cite this article as: Sertpoyraz FM, Colak A, Dikici A, Erdinc Gunduz N, Zeytinli Aksit M. The relationship of ischemia-modified albumin levels to disease activity scores and HLA-B27 in patients with ankylosing spondylitis. North Clin Istanb UNCORRECTED PROOF A nkylosing Spondylitis (AS) is a chronic rheumatic disease that is characterized by inflammatory low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…A major finding of the present study was that patients with AS had significantly higher serum IMA level than controls. This finding is in agreement with the findings of a previous study that compared the serum IMA level between 63 patients with AS and 48 controls and found that the AS patients had significantly higher IMA levels than controls [27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A major finding of the present study was that patients with AS had significantly higher serum IMA level than controls. This finding is in agreement with the findings of a previous study that compared the serum IMA level between 63 patients with AS and 48 controls and found that the AS patients had significantly higher IMA levels than controls [27].…”
Section: Discussionsupporting
confidence: 93%
“…In the study of Sertpoyraz et al the CRP and IMA levels were high in patients with active AS, and there was a positive correlation between them [45]. Consistent with these findings, it was previously found that high CRP values were associated with radiological changes and SIj inflammation and correlated with the BASDAI scores [46].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In many studies, it has been shown that serum IMA level is higher than HC in rheumatological diseases such as RA and AS and is associated with disease activity. [40][41][42][43] In our study, serum IMA levels were found to be similar between SLE patients and HCs. But serum IMA levels were found to be higher in SLE patients with HDA compared to LDA.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, ischemia-modified Alb (IMA) is a type of Alb with an altered structural conformation of the N-terminus of Alb that increases upon exposure to ischemia, hypoxia, oxidative stress, and inflammation [ 8 ]. Although IMA was initially recognized as a biological marker increased in acute coronary syndrome, research has demonstrated that IMA is also elevated in patients with autoimmune disorders such as inflammatory bowel diseases, Behcet disease, and ankylosing spondylitis [ 9 11 ]. Nonetheless, the correlation between disease activity and indices of Alb, Palb, and IMA has not been investigated in patients with AAV.…”
Section: Introductionmentioning
confidence: 99%